CREATIVE CONTEMPORARY PAINTING BASED ON THE ICONOGRAPHY OF YEH PULU RELIEF - I Wayan Adnyana (Proceeding IICACS, 2019)
This paper is a report of creative art research under the program of Researching, Creating and Presenting Art of the Research, Technology and Higher Education Ministry of Indonesia. The subject of this research is an iconographic people‟s hero of Yeh Pulu relief. This relief is an ancient artifact of Balinese art, located in Bedulu, Gianyar Regency. Visual analysis of the Panofsky‟s iconography method (D‟alleva, 2005: 22-23) is used as a means of iconography analysis with three aspects: visual/artistic characters, allegories, and symbols. The first-year of the study focuses on analyzing the fundamental visual/artistic approach of my new of contemporary painting series. Deep analysis revealed five findings of visual/artistic approach that explore this theme as the newest visual art concept: cutting (imagining the relief like a poster); smashing (the natural effect of the relief being broken down into many small pieces); drawing (incorporating the visuals of a relief in the method of drawing); highlighting (like a macro camera that presents the profile in its largest and most detailed capacity); coloring (using color to make the visuals impressionistic). The research members are: A. A. Bagus Udayana (photographer), I Nengah Sudika (data collector), and Desi In Diana Sari (layout designer).Keywords: Iconography, People‟s hero, Yeh Pulu relief, Visual/artistic approach